2005
DOI: 10.1080/13506280444000599
|View full text |Cite
|
Sign up to set email alerts
|

The use of visual information in natural scenes

Abstract: Despite the complexity and diversity of natural scenes, humans are very fast and accurate at identifying basic-level scene categories, In this paper we develop a new technique (based on Bubbles. Gosselin & Schyns. 2001 as Schyns, Bonnar, & Gosselin, 2002) to determine some of the information requirements of basic-level scene categorizations, Using 2400 scenes from an established scene database the Fourier coefficients (Oliva & Torralba, 2001). the algorithm randomly samples the Fourier coefficients of the phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…It is important to note that the cut-off frequency used to filter LSF scenes in the present study (4 cpd, i.e., 24 cpi) was relatively high as compared to the ones used in previous studies (usually around 2 cpd; see Kauffmann, Bourgin, et al, 2015;Mu & Li, 2013;Schyns & Oliva, 1994). LSF scenes in the present study thus included a rather large part of the scene spatial frequency spectrum including low to intermediate spatial frequencies and therefore contained the most diagnostic features for scene and object categorization, which have be found to lie at 0-4 cpd (see Caplette et al, 2014;McCotter et al, 2005). Therefore, it is likely that the advantage for LSF processing observed in the present study also reflects the fact that the LSF scenes contained the most relevant information for categorization.…”
Section: Low Spatial Frequency Processing Advantagementioning
confidence: 47%
See 1 more Smart Citation
“…It is important to note that the cut-off frequency used to filter LSF scenes in the present study (4 cpd, i.e., 24 cpi) was relatively high as compared to the ones used in previous studies (usually around 2 cpd; see Kauffmann, Bourgin, et al, 2015;Mu & Li, 2013;Schyns & Oliva, 1994). LSF scenes in the present study thus included a rather large part of the scene spatial frequency spectrum including low to intermediate spatial frequencies and therefore contained the most diagnostic features for scene and object categorization, which have be found to lie at 0-4 cpd (see Caplette et al, 2014;McCotter et al, 2005). Therefore, it is likely that the advantage for LSF processing observed in the present study also reflects the fact that the LSF scenes contained the most relevant information for categorization.…”
Section: Low Spatial Frequency Processing Advantagementioning
confidence: 47%
“…For example, different spatial frequency bands would be used according to their diagnosticity to categorize a specific visual stimulus. It has been shown that spatial frequencies below 2 cpd are diagnostic to perform basic-level categorization of scenes (e.g., forest, highway, mountain; McCotter, Gosselin, Sowden, & Schyns, 2005). However, intermediate spatial frequencies of 2.3-4 cpd would be required for basic-level categorization of objects (Caplette et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Visual search is facilitated when there is a correlation across different trials between the contextual configuration of the scene display and the target location (Brockmole & Henderson, 2006b;Chun & Jiang, 1998Eckstein et al, in press;Hidalgo-Sotelo et al, 2005;Jiang & Wagner, 2004;Oliva et al, 2004;Olson & Chun, 2002). In a similar vein, several studies support the idea that scene semantics can be available early in the chain of information processing (Potter, 1976) and suggest that scene recognition may not require object recognition as a first step (Fei-Fei & Perona, 2005;Greene & Oliva, 2006;McCotter et al, 2005;Oliva & Torralba, 2001;Schyns & Oliva, 1994). The present approach proposes a feedforward processing of context (see Figure 1) that is independent of object-related processing mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…For example, many studies have presented observers with a target class of scenes, such as scenes containing animals (Thorpe et al, 1996) or forest scenes (Greene & Oliva, 2009), and have asked observers to detect target scenes among the nontarget distractor scenes. However, such explicit categorization tasks provide a strong top-down signal biasing visual processing toward features that are diagnostic of the target class (Johnson & Olshausen, 2003;McCotter, Gosselin, Sowden, & Schyns, 2005). In other words, if an observer reports seeing (e.g.)…”
mentioning
confidence: 99%